2013
DOI: 10.1128/jb.00058-13
|View full text |Cite
|
Sign up to set email alerts
|

Fe(II) Oxidation Is an Innate Capability of Nitrate-Reducing Bacteria That Involves Abiotic and Biotic Reactions

Abstract: Phylogenetically diverse species of bacteria can catalyze the oxidation of ferrous iron [Fe(II)] coupled to nitrate (NO 3؊ ) reduction, often referred to as nitrate-dependent iron oxidation (NDFO). Very little is known about the biochemistry of NDFO, and though growth benefits have been observed, mineral encrustations and nitrite accumulation likely limit growth. Acidovorax ebreus, like other species in the Acidovorax genus, is proficient at catalyzing NDFO. Our results suggest that the induction of specific F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
162
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(171 citation statements)
references
References 68 publications
8
162
1
Order By: Relevance
“…For the cultivated mixotrophic nitratereducing Fe(II) oxidizers, it could be that Fe(II) oxidation is not an enzymatic process but an abiotic side reaction caused by nitrite that is formed during heterotrophic denitrification (27). It could even be that this side reaction is unavoidable during denitrification in the presence of Fe(II) (28). Thus, such indirect Fe(II) oxidation could be important in nitrate-and organic-rich marine sediments, such as in Norsminde Fjord.…”
Section: Coexistence Of Different Physiological Types Of Fe(ii) Oxidimentioning
confidence: 99%
See 1 more Smart Citation
“…For the cultivated mixotrophic nitratereducing Fe(II) oxidizers, it could be that Fe(II) oxidation is not an enzymatic process but an abiotic side reaction caused by nitrite that is formed during heterotrophic denitrification (27). It could even be that this side reaction is unavoidable during denitrification in the presence of Fe(II) (28). Thus, such indirect Fe(II) oxidation could be important in nitrate-and organic-rich marine sediments, such as in Norsminde Fjord.…”
Section: Coexistence Of Different Physiological Types Of Fe(ii) Oxidimentioning
confidence: 99%
“…For these mixotrophic strains, it is not yet known whether Fe(II) oxidation is just a chemical side reaction with nitrite, which is produced during heterotrophic denitrification (26,27), or if it is an enzymatic reaction from which the bacteria can gain energy. Interestingly, Fe(II) oxidation seems to be a universal ability of all NO 3 Ϫ -reducing bacteria when an organic substrate is provided (28). A unique feature of this group of Fe(II) oxidizers is that the cells become encrusted with Fe(III) minerals during Fe(II) oxidation (27), a process that is potentially harmful to the cells (29).…”
mentioning
confidence: 99%
“…Evidence for an enzymatic Fe(II) oxidation was provided by Chakraborty and Picardal (23), who found that Fe(II) oxidation is inducible at an enzymatic level for Acidovorax strain 2AN. In contrast, Carlson et al (50) did not see inducible Fe(II) oxidation for Acidovorax ebreus strain TPSY, and in a proteomic study with the same strain, those authors did not find any specific proteins responsible for Fe(II) oxidation. Although the main question therefore still remains whether in these strains Fe(II) oxidation may be caused partly or even completely by an abiotic reaction with nitrite/NO, our present study showed that ordinary nitrate-reducing bacteria show nitrite accumulation and Fe(II) oxidation rates similar to those of two nitrate-reducing strains that were isolated as Fe(II) oxidizers.…”
Section: Discussionmentioning
confidence: 76%
“…Their use as an electron acceptor in anaerobic microbial metabolism is more thermodynamically favourable than ferric oxides (Hyacinthe and Van Cappellen 2004). Conversely, ferrous phosphates have been shown to be sensitive to rapid oxidative dissolution and precipitation as ferric phases in the presence of oxygen (e.g., Roldán et al 2002) and by nitrate-reducing, iron-oxidizing bacteria (Miot et al 2009;Carlson et al 2013).…”
Section: Dissolutionmentioning
confidence: 99%